Barry Bingham : a man of his word - Bingham, Barry, 1906-1988 (Kentucky remembered., 2015)
Barry Bingham, Sr., was one of this country's most influential journalists. Under his half-century of leadership, the Louisville Courier-Journal became one of America's leading newspapers, as attested by six Pulitzer Prizes. In this illuminating oral history, Samuel Thomas weaves together excerpts from more than a dozen interviews with Bingham, along with selections from his writings and comments by his wife, Mary Caperton Bingham. Barry Bingham's influence was voiced principally through newspaper journalism, but, besides owning the Courier-Journal and its evening companion, the Louisville T.